2021
DOI: 10.3389/fnins.2021.709482
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Based Amplitude of Low-Frequency Fluctuation Alterations in Patients With Tinnitus Before and After Sound Therapy: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: This study aimed to investigate abnormal tinnitus activity by evaluating brain surface-based amplitude of low-frequency fluctuation (ALFF) changes detected by resting-state functional magnetic resonance imaging (RS-fMRI) in patients with idiopathic tinnitus before and after 24 weeks of sound therapy. We hypothesized that sound therapy could gradually return cortical local brain function to a relatively normal range. In this prospective observational study, we recruited thirty-three tinnitus patients who had un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…The authors found a pattern of increased and reduced glycolitic metabolism in many regions throughout the cortex. The neural correlates of sound therapy were evaluated by a single group, by measuring variation of grey matter thickness [87], of white matter volume [88] and amplitude of the low frequency fluctuations [89]. These studies found different modifications, however without showing a clear pattern of coherent results.…”
Section: Perspectives For Treatment Of Tinnitusmentioning
confidence: 99%
“…The authors found a pattern of increased and reduced glycolitic metabolism in many regions throughout the cortex. The neural correlates of sound therapy were evaluated by a single group, by measuring variation of grey matter thickness [87], of white matter volume [88] and amplitude of the low frequency fluctuations [89]. These studies found different modifications, however without showing a clear pattern of coherent results.…”
Section: Perspectives For Treatment Of Tinnitusmentioning
confidence: 99%
“…In contrast with conventional rs-fMRI methods, a 360-area surface-based cortical segmentation based on the Human Connectome Project (HCP) leads to the analysis of spatial localization of cortical areas, is highly sensitive and specific, improves the accuracy of region alignment by three times [32], and reduces the effect of spatial smoothing [32]. Recently, surface-based ALFF and two-dimensional regional homogeneity were used to investigate abnormal brain function patterns in patients with idiopathic tinnitus [35] and schizophrenia [36], respectively. In addition, subcortical brain regions are known to be involved in mood and cognitive processing [37, 38].…”
Section: Introductionmentioning
confidence: 99%